2019
DOI: 10.1089/tmj.2018.0027
|View full text |Cite
|
Sign up to set email alerts
|

Tele-Emergency Services in the Himalayas

Abstract: Preliminary analysis confirms that delivering TES in inhospitable terrains in a Public Private Partnership mode is doable and is welcomed by the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
0
24
0
1
Order By: Relevance
“…Ganapathy et al, 2016 [ 50 ] Range of specialist services → remote hospitals VC, S&F Kaza/Keylong, India 7 S 17. Ganapathy et al, 2019 [ 51 ] Tele-emergency services → remote hospitals VC, S&F Kaza/Keylong, Northern India 3 S 18. Ganapathy et al, 2020 (online in 2019) [ 52 ] Teleconsultations, screening services for noncommunicable diseases → regional areas VC, S&F Six regions in India 5 S 19.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ganapathy et al, 2016 [ 50 ] Range of specialist services → remote hospitals VC, S&F Kaza/Keylong, India 7 S 17. Ganapathy et al, 2019 [ 51 ] Tele-emergency services → remote hospitals VC, S&F Kaza/Keylong, Northern India 3 S 18. Ganapathy et al, 2020 (online in 2019) [ 52 ] Teleconsultations, screening services for noncommunicable diseases → regional areas VC, S&F Six regions in India 5 S 19.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty studies identified the importance of coordinators for facilitating telemedicine services. Coordinators played an important role in preparing the organization for change [43,51], scheduling and integrating telemedicine activities into clinical workflow patterns [56], liaising with participating stakeholders [49], troubleshooting technical issues [18,56] and overseeing quality control of the service [56]. Frequent communication with telemedicine coordinators was shown to be vital in sustaining a telemedicine program, with one study reporting that telemedicine services ceased when the coordinator left [37].…”
Section: Phase 1 Preparing For Change -Operational Practicesmentioning
confidence: 99%
“…It is evident that city and urban areas in both countries have more reliable ICT infrastructure and connectivity than those found in rural and remote regions. Given that one of the aims of telehealth is to diagnose and treat patients who live in these regions and who are not able to travel to cities and large towns, the unreliability of ICT inhibits both the transmission of quality images to telehealth centers [8,10,25,27] and the transfer of images between healthcare professionals. Finally, the improvement in hand-held devices can be seen as a major driver in improving the image quality sent by the patients to the doctors [60], however, lack of patient knowledge of how to use the inbuilt camera and different apps for transferring digital images greatly decreases the quality of the images when compared with those taken by health care professionals.…”
Section: Resultsmentioning
confidence: 99%
“…There have been a range of studies, conducted in India and Pakistan regarding the adoption of ICT within the healthcare domain [25][26][27][28][29][30][31][32][33][34][35][36]. Chandwani, Dwivedi [37] suggested challenges in the adoption of telemedicine can be classified across policy, societal, institutional and medical infrastructural levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2019). Telemedicine services in PPP have been effective and successful under diverse geographic and socio-economic settings in the country including inaccessible and remote areas of Himachal Pradesh (Ganapathy et al, 2016;Ganapathy, 2014;Ganapathy et al, 2018;CSC Annual Report 2015-16). Apollo Telehealth Services (ATHS), Medanta Hospital are the leading stakeholders in providing telemedicine services in PPP mode (Ganapathy et al, 2016;Ganapathy, 2014;Ganapathy et al, 2018;CSC Annual Report 2015-16).…”
Section: Challenges and Barriersmentioning
confidence: 99%